Implementasi Kebijakan Eliminasi Malaria Di Pusat Kesehatan Masyarakat Kota Kupang - Pius Selasa (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2017)
Malaria is one of the contagious infectious diseases which is still a global public health problem. Of the 106 countries endemic malaria in the world, Indonesia entered the top 10 endemic countries (Hay, 2007). Recorded 214 million malaria cases (confirmed) worldwide and 306 thousand under-five deaths in the world due to Malaria (WHO, 2014). Indonesia reported there were 343 thousand cases of Malaria (confirmed) (Ministry of Health, 2014) and East Nusa Tenggara Province 36,128 cases (Health Department, 2016). Nationally, 75-80% of malaria cases in Indonesia come from eastern Indonesia (Papua, West Papua, Maluku, North Maluku and East Nusa Tenggara). Various efforts have been made to reduce morbidity and mortality due to malaria, among others, with the policy of elimination of Malaria both globally, nationally and locally. The purpose of this research is to know the description of the implementation of malaria elimination policy at Public Health Center of Kupang City. The type of this research is quantitative research that describes the implementation of malaria elimination policy in Public Health Center with the Descriptive design. The data of the research were analyzed descriptively and presented in the form of frequency distribution and percentage. The results showed that the discovery and management of patients, Prevention and control of risk factors, epidemiological surveillance and epidemic control, Improving communication, information and education, and Increasing human resources in implementation the policy of eliminating malaria at the Kupang Public Health Center is implemented in accordance with the stipulated policy of reaching 100% for 11 Public Health Center.